Pengaruh ROA dan Firm Size Terhadap DPR Dengan Corporate Governance Sebagai Variabel Intervening - Erika Debora Tambunan; Rizki Fillhayati Rambe; Ruswan Nurmadi (Jurnal Studi Akuntansi Pajak Keuangan, 2024)
This research aims to determine Return on Asset and Firm Size on Dividend Payout Ratio with Corporate Governance as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 - 2021. The sample selection method used is purposive sampling. The total observations in this research were 155 observations consisting of 31 companies. The data analysis technique used in this research is path analysis with the SPSS version 26 analysis tool. The results of testing sub structure I show that Return on Asset has a positive effect on Corporate Governance. Meanwhile, Firm Size has no effect on Corporate Governance. The results of sub-structure II testing show that Return on Asset has a positive effect on Dividend Payout Ratio and Corporate Governance has a negative effect on Dividend Payout Ratio, while Firm Size has no effect on Dividend Payout Ratio. The sobel test results show that Corporate Governance is able to mediate the effect of Return on Asset on Dividend Payout Ratio. Meanwhile, Corporate Governance is not able to mediate the effect of Firm Size on the Dividend Payout Ratio.